2014
DOI: 10.1002/2014wr015595
|View full text |Cite
|
Sign up to set email alerts
|

Global‐scale assessment of groundwater depletion and related groundwater abstractions: Combining hydrological modeling with information from well observations and GRACE satellites

Abstract: Groundwater depletion (GWD) compromises crop production in major global agricultural areas and has negative ecological consequences. To derive GWD at the grid cell, country, and global levels, we applied a new version of the global hydrological model WaterGAP that simulates not only net groundwater abstractions and groundwater recharge from soils but also groundwater recharge from surface water bodies in dry regions. A large number of independent estimates of GWD as well as total water storage (TWS) trends det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
574
2
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 641 publications
(594 citation statements)
references
References 79 publications
16
574
2
2
Order By: Relevance
“…Globally, around half of pumped groundwater for irrigation is used by plants, whereas the remainder possibly flows to the ocean as runoff causing SLR; evaporates into the atmosphere increasing water vapour content; returns back to the aquifers through groundwater recharge; or affects the atmospheric circulation owing to surface energy modifications and changes the precipitation intensity or pattern locally, regionally and globally 9,27,28 . In this study, we used the state-of-the-art fully coupled NCAR CESM 11 version 1.0.3 to simulate the fate of water pumped from groundwater and calculate the relative proportion of GWD to the sea-level changes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, around half of pumped groundwater for irrigation is used by plants, whereas the remainder possibly flows to the ocean as runoff causing SLR; evaporates into the atmosphere increasing water vapour content; returns back to the aquifers through groundwater recharge; or affects the atmospheric circulation owing to surface energy modifications and changes the precipitation intensity or pattern locally, regionally and globally 9,27,28 . In this study, we used the state-of-the-art fully coupled NCAR CESM 11 version 1.0.3 to simulate the fate of water pumped from groundwater and calculate the relative proportion of GWD to the sea-level changes.…”
Section: Methodsmentioning
confidence: 99%
“…The previous work suggests that a rapid increase in the contribution of GWD to SLR has occurred in recent decades (0.31-0.57 mm yr −1 ) [7][8][9] . An increasing contribution from land waters to SLR is in fact noted in the IPCC Fifth Assessment Report (IPCC AR5) 4 ; however, the uncertainty remains substantially large.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…At each temporal scale, some processes may be more relevant than others. For example, decadal trends can be controlled by groundwater depletion [Döll et al, 2014;Chen et al, 2016] or ice melt [Jacob et al, 2012;Velicogna et al, 2014], whereas short-term anomalies are usually related to fluctuations of the relevant atmospheric drivers [Humphrey et al, 2016]. We therefore decompose the TWS signal in order to relate changes in water storage to changes in atmospheric drivers at the temporal scales at which they are the most relevant.…”
Section: Decomposition Into Temporal Componentsmentioning
confidence: 99%
“…Simulated TWS variations can also be validated by continuous GPS observations at more than 200 network stations worldwide because water storage variations cause crustal deformations which lead to displacements of the GPS reference point (Döll et al 2014b). Comparing simulated TWS variations against both GRACE and GPS, Döll et al (2014b) identified regions where the WaterGAP GHM underestimates seasonal variability of TWS and found that maximum TWS occurs 1 month too early in WaterGAP for most land areas (based on GRACE only). Validating groundwater depletion as computed by WaterGAP against both in situ well observations and GRACE TWS allowed the conclusion that farmers in groundwater depletion area irrigate with only 70 % of the optimal value (Döll et al 2014a).…”
Section: Multi-criteria Validation Against River Discharge and Geodetmentioning
confidence: 99%